DEVELOPMENT OF HARD FUEL PREPARING FOR THERMAL TREATMENT OF SINTERING MIXTURE - Mnykh, Anton; Pazyuk, Mikhail; Ovchinnikova, Irina; Baryshenko, Elen (Scientific Journal "Metallurgy", 2021)
The of more micronizing of coke change, that results in the decline of mechanism of crushing of sintering mixture are investigated in-process in an ag-gregate with the purpose of optimization of its work and also feature of burning of hard fuel in the process of agglomeration. A basic energy of sintering process source is warmth of hard fuel burning as which is a coke change or anthracite culm. Preparation of fuel consists in its growing shallow to the required factious composition in crushing-crumbling setting. Dependences between a temperature in the area of burning and gas dynamics of layer for sintering mixture from fac-tionalism of the used fuel, and also between intensity of burning and composition of gases in the area of burning are set. It is educed, that at burning of coke change a largeness a 0,5…3,0 mm more high temperature is fixed as compared to faction a 3,0…5,0 mm; intensity of burning increases because mailtenance of carbon monoxide in off-gas. The chart of process of crushing of hard fuel is described in a four-high crusher and describing this process system of equalities. The series of experiments on growing of coke change and culm shallow for determination of the optimal productivity of crusher are carried out. The analysis of the got results shows that at the stable mode of crushing the spectrum of factionalism of the crushed fuel depends on its natural properties. The researches on fixing time of burning down of standard faction of hard fuel are carried out. Researches of crushing mechanism in a rolling aggregate allowed to draw conclusion about the necessity of change of chart of crushing of fuel with its preliminary classification for the purpose of decline of influence of the wearing down loading on the ground down material.